Duan Lolat: Tanimbar Traditional Marriage Traditions from the Perspective of Law and Modernity - Taborat, Alowisius; Roberth KR Hammar; Agustinus Luturmas (Manunggal Halim Jaya, 2025)
The Duan Lolat traditional marriage in the Tanimbar community is a tradition that contains high philosophical, social, and cultural values. This tradition not only functions as a form of binding two extended families, but also as a means of preserving cultural identity and strengthening solidarity between indigenous communities. This study aims to examine the philosophical meaning and implementation process of Duan Lolat and its legal position in the national legal system, and identify challenges and efforts to preserve it in the modern era. Using a normative and anthropological juridical approach, it was found that although Duan Lolat is constitutionally recognized through Article 18B paragraph (2) of the 1945 Constitution and has high social relevance, its practice still faces legal dualism and minimal guarantees of civil protection, especially for women and children. Therefore, harmonization between customary and national law is needed through a mechanism for registering customary marriages integrated into the state administration system and strengthening customary institutions and cultural education for the younger generation as a preservation strategy.